Specific image of the Church and evangelization in saint Bede the venerable's commentary on the Apocalypse - Dariusz Sztuk (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Numerous passages of the Book of Revelations, beginning with the prologue (Rev. 1), through letters to the seven Churches (Rev. 2-3), to the vision of the Heavenly Jerusalem (Rev. 21), accentuate the image of the Church as well as the role of God's word and the issuing necessity to preach it. Those themes found their reflection in the Commentary on the Apocalypse, composed by Bede the Venerable in the first period of his erudite exegetical creative output. This article, in three subsequent stages presents the following themes: 1) the image of the Church; 2) proclamation of the word of God by the Church; 3) attributes and tasks of God's word preachers.